2011
DOI: 10.1007/s11695-011-0532-9
|View full text |Cite
|
Sign up to set email alerts
|

Biliopancreatic Diversion with Roux-en-Y Gastric Bypass and Long Limbs: Advances in Surgical Treatment for Super-obesity

Abstract: Our variant of biliopancreatic diversion (BPD-RYGB-LL) results in substantial and sustained weight loss in super-obese, without compromising safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 34 publications
(74 reference statements)
1
17
0
4
Order By: Relevance
“…The online version of this article (https://doi.org/10.1007/s11695-018-03686-3) contains supplementary material, which is available to authorized users. pouch, there are two limb characteristics of RYGB: one is the alimentary limb where food passes and the other is the biliopancreatic limb which permits biliopancreatic secretion [5]. Despite of its effectiveness, the underlying mechanisms resulting in weight loss and metabolic improvements remain not adequately understood.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…The online version of this article (https://doi.org/10.1007/s11695-018-03686-3) contains supplementary material, which is available to authorized users. pouch, there are two limb characteristics of RYGB: one is the alimentary limb where food passes and the other is the biliopancreatic limb which permits biliopancreatic secretion [5]. Despite of its effectiveness, the underlying mechanisms resulting in weight loss and metabolic improvements remain not adequately understood.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…It is thought that the length of the common limb affects the malabsorption and herewith the amount of weight loss (18)(19)(20)(21) , but possibly also leading to nutrient and vitamin deficiencies (22)(23)(24)(25) . A systematic review by Orci et al in 2011 identified a trend supporting that the construction of a longer Roux limb was more effective in super obese patients in terms of weight loss, and no differences were found regarding nutritional outcomes between groups (26) .…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly important given that higher PA levels and positive PA attitudes and beliefs preoperatively are associated with higher PA levels postoperatively (1,3,29) . Moreover, previous studies involving use of similar objective PA measures show that postoperative patients, despite the benefits of bariatric surgery, do not reach the level of bout-related MVPA achieved by the intervention participants in the current preoperative study (4,5) .…”
Section: Discussionmentioning
confidence: 99%